Does cognitive distance affect product development for distant target groups? Evidence from the literature using co-citation methodology - Jia Hui Lew; Malte Marwede; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2015)
The level of cognitive distance determines how detailed objects, persons or events are mentally construed. The higher the level of cognitive distance between two individuals, the lower the level of detail in mental representation of each other. In product development, a detailed conception of the target group is essential for future product success. Product developers need to establish an accurate mental representation of the user and internalize customer preferences to ensure product usability and/or delivery of adequate services in new product development projects (NPD). Depending on the target group in focus, potential users can be distant in various dimensions. Silver Agers (65+ years of age) can be a distant target group for product developers in terms of age and personal contacts as most developers are too young to fall in the category of Silver Agers. Thus, they have likely taken different life experience paths compared to people of their own age cohort. Management and psychological science refers to this phenomenon as cognitive or psychological distance. Especially for distant target groups (e.g. elderly people or children), cognitive distance between product developers and users might have an impact on the creation of new products/services. Literature in this field, especially within an innovation context, is very scarce. Therefore, this paper analyzes existing research streams and thought schools of cognitive distance literature and their applicability in an innovation context to study implications for NPD. We use co-citation analysis to identify and visualize the different research areas dealing with cognitive distance, and to detect conceptual subdomains applicable for individual relationships between product developers and (distant) target groups. We find eight relevant clusters dealing with cognitive distance in psychology and innovation management-related research papers. Construal level theory stands out as the predominant theoretical foundation of cognitive distance in psychological research. It states that distant persons, objects or events in terms of space, time, social or probability are mentally construed in a more abstract way as opposed to nearer/closer/more likely persons, objects or events. Applied to product developers' mental representation of the actual users, this infers that users of distant target groups are likely to be represented more abstractly compared to proximal target groups, e.g. target groups of similar age. This lesser differentiated view on users could lead to non-optimal solutions in NPD. We thus propose that cognitive distance can have an impact on product development. We discover a knowledge gap on the individual level for innovation management studies, i.e. linking cognitive distance to product development success. We analyze findings from psychological research on individual cognitive distances and find that besides temporal distance, the social dimension of cognitive distance appears to be most relevant for empirical tests in innovation management. To empirically explore and test dimensions of social distance, we argue to utilize established network-theoretic measures, like social capital as a proxy for social distance between product developers and distant target groups. We close with practical suggestions to mitigate adverse effects of cognitive distance for product developers.
Keywords: 330; cognitive distance; psychological distance; Silver Market; distant target group; innovation management